"He slew the Egyptian and hid him in the sand": Jewish tradition and the moral element - Śagiʾ, Avraham (Hebrew Union College annual / Jewish Institute of Religion, 1996)
The concern of this article is the struggle of Jewish tradition with the immorality of Moses' killing of the Egyptian. The various approaches to this question allow us to make inferences about the status of morality in Judaism. These approaches can be classified under two main rubrics — the amoral trend and the moral trend. The amoral trend assumes that Moses' behavior poses no moral problem, while the moral trend assumes that we must examine Moses' behavior in the light of standard moral criteria. This trend is manifest in the suggestion of moral justifications for Moses' behavior on the one hand, and in open moral criticism on the other. Common to all approaches is the rejection of the possibility that morality depends on religion. Although the amoral approach assumes that Moses' behavior is moral and requires no justification, it never claims that we face no problem because religion determines what is moral. This study, then, supports the claim that Jewish tradition endorses the theory that morality is autonomous rather than one stating that morality depends on religion.